Local Democracy without Elections: The Politics in Nepal - Chetri, Than Bahadur (Journal of Political Science, 2017)
The article analyzes the nature of perversion at local level in the absence of poll, controversy and conflict in local transition of Nepal at the present context. It also argues that the absence of elections at micro democratic institutions, right to vote and elect own representatives remain on paper, poor service delivery and no service delivery, the relation between the state and the citizens have further widened due to legacy of exclusionary politics. At the end, political parties are the creator of democracy; they lack a common vision to lead the society and how to live together. Federalism a new political order, is going to start; the coming days will show whether it will bring stability or instability in such society. Journal of Political Science. Vol. 17, 2017, Page: 63-81